(untitled) (Journal of Economics and Management Research, 2025)
This research paper aims to discuss the financial depth in Algeria by presenting the most important indicators and variables representing the depth and size of financial intermediation during the period from 1990, which is the beginning of financial and monetary reforms in Algeria, until 2021 (data availability). The study used different variables, the financial depth index from the International Monetary Fund data and variables from the World Bank database. Through the analytical study, which consisted of tracking the movement and path of these indicators during the study period, we concluded that the financial intermediation of Algerian banks is still suffering from low levels of financial size and depth.